2016
DOI: 10.20471/acc.2016.55.s1.01
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Difficult Airway Management in Thyroid Surgery: A Five-Year Observational Single-Center Prospective Study

Abstract: SUMMARY -Difficult tracheal intubation (DI) is more common in thyroid than in other surgical branches due to thyromegaly. Proper preoperative airway evaluation is necessary in order to reduce the potential numerous complications. The study examined the incidence of DI in thyroid surgery and the influence of tracheal dislocation and other risk factors on DI. A prospective study was conducted on 2379 patients who underwent thyroidectomy at the Center for Endocrine Surgery, Clinical Center of Serbia, from 2007 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…That study considered only radiological tracheal configuration in predicting DI ( 14 ). In the study by Kalezic et al ( 17 ), tracheal deviation and stenosis were shown to be significant but not independent predictors of DI in thyroid surgery. The observed difference from our study may be due to our smaller sample size and the duration of study which was three years.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…That study considered only radiological tracheal configuration in predicting DI ( 14 ). In the study by Kalezic et al ( 17 ), tracheal deviation and stenosis were shown to be significant but not independent predictors of DI in thyroid surgery. The observed difference from our study may be due to our smaller sample size and the duration of study which was three years.…”
Section: Discussionmentioning
confidence: 88%
“…Their study had a total sample size of 2,379 patients who had surgery over a period of five years in a centre dedicated to endocrine surgery. Kalezic et al ( 17 ) reported that tracheal dislocation and/or stenosis was more present in the group with DI. The authors gave this as the reason for preoperative x-ray before thyroid surgery in their centre.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the incidence of difficult intubation of the trachea is higher in thyroid surgery compared to other types of surgery. The incidence of difficult intubation in our previous studies, which included more than 2,000 patients who underwent thyroid surgery, were 5.5% and 6.81%, respectively [25,26], while Adnet et al [27] and Amathieu et al [28] reported even higher incidence (8% and 11.1%, respectively). In this study, difficult intubation was registered in 12.2% of patients.…”
Section: Discussionmentioning
confidence: 65%
“…There are conflicting study results about the most predictive DTI risk criteria in patients undergoing thyroid surgery [37]. Neck circumference (NC) seems to be an important predictor for DTI in this population of patients [57]. A study of a large cohort of patients undergoing thyroidectomy found that the size of the neck (circumference and length) is one of most important independent predictors of DTI in thyroid surgery [5].…”
Section: Introductionmentioning
confidence: 99%
“…Neck circumference (NC) seems to be an important predictor for DTI in this population of patients [57]. A study of a large cohort of patients undergoing thyroidectomy found that the size of the neck (circumference and length) is one of most important independent predictors of DTI in thyroid surgery [5]. Cut-off values for neck width have not been established.…”
Section: Introductionmentioning
confidence: 99%